Exploration Of Social Exchange Theory: Costumer Loyalty with Trust And Satisfaction As Intervening in Islamic People's Financing Banks (BPRS) - Lubis, Adelina; Effendi, Ihsan; Rosalina, Dhian; Murad, Miftahuddin (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
This research was at the Medan City Islamic People's Credit Bank (BPRS), which was lagging in terms of the number of customers and information technology. This study aims to determine the effect of organizational information and information technology on loyalty by using the intervening variables of satisfaction and trust. This research used correlational quantitative and Structural Equation Models (SEM). Respondents used in this study were 314 BPRS customers who are still active. The results showed that the information technology used by the BPRS did not affect loyalty where satisfaction was the intervention variable. On the other hand, organizational communication had an influence on customer loyalty with customer trust as an intervention variable